Population Pharmacokinetic/Pharmacodynamic Analysis of Intravenous Zanamivir in Healthy Adults and Hospitalized Adult and Pediatric Subjects With Influenza. Issue 1 (7th November 2019) - Zuo, Peiying; Collins, Jon; Okour, Malek; Barth, Aline; Shortino, Denise; Yates, Phillip; Roberts, Grace; Watson, Helen A.; Peppercorn, Amanda; Hossain, Mohammad
Abstract : Zanamivir is a potent and highly selective inhibitor of influenza neuraminidase in which the inhibition of this enzyme prevents the virus from infecting other cells and specifically prevents release of the new virion from the host cell membrane. It is available as an oral powder for inhalation and intravenous formulations. The current population pharmacokinetic model based on data from eight studies of subjects treated with the intravenous formulation (125 healthy adults and 533 hospitalized adult and pediatric subjects with suspected or confirmed influenza) suggested a decreased zanamivir clearance in pediatric and renal impairment adult subjects. It also indicates that b.i.d. dosing is necessary to keep the exposure in influenza infected subjects above the 90% inhibitory concentration values of recently circulating viruses over the dosing interval. In the exposure‐response analysis (phases II and III studies), no apparent relationship was found between zanamivir exposure and clinically relevant pharmacodynamic end points.